Hukum Tata Pemerintahan dan Pencegahan Korupsi - Halim, Hifdzil (UIN Sunan Kalijaga Yogyakarta, 2012)
Government free of corruption starting with government free of corruption aswell. To create a clean government, should begin by establishing an anti-corruptionpolicies, either the policy or the policy is at the center of that area. Errors in shapinggovernment policy, will open the faucet corruption. The legislation of governance (HTP)and good governance (good governance) is believed to be directing policy for the benefit ofthe community and avoid corruption.